Prognostic Value of Combined Preoperative Carcinoembryonic Antigen and Prognostic Nutritional Index in Patients With Stage II–III Colon Cancer - Xu, Yan-song; Liu, Gang; Zhao, Chang; Lu, Shao-long; Long, Chen-yan; Zhong, Hua-ge; Chen, Yi; Huang, Ling-xu; Liang, Zheng (Frontiers in Surgery, 2021)
Background: In addition to the status of the tumor can affect the patient's prognosis. As a nutritional indicator, prognostic nutritional index (PNI) is strongly associated with cancer prognosis. However, there is a lack of the combined prognostic value of carcinoembryonic antigen (CEA) and PNI in patients. We examined the association between CEA/PNI and colon cancer patient’s prognosis. Patients and methods: 463 patients with stage II-III colon cancer who underwent curative resection at two medical centers from 2009 to 2019 were included. Clinicopathological factors were assessed in a learning set of 413 patients, and the overall survival (OS) rate was evaluated. Multivariate analyses were used to identify independent prognostic variables for the construction of a nomogram to predict 1-year OS and 3-year OS. 50 independent patients from the validation set were used to validate the prognostic model. Results: The median OS time was 33.6 months, and mortality was observed in 54 patients. Multivariate analysis revealed that preoperative CEA/PNI, lymph node metastasis, peripheral nerve invasion, operation mode, and postoperative chemotherapy were independent factors for evaluating prognosis. These variables were used to develop the nomogram. The C-index was 0.788 in the learning set and 0.836 in the validation set. The calibration curves reached a good consensus between the 1-year, 3-year OS prediction and actual observation. Conclusions: The combined use of CEA together with PNI is an independent prognostic factor, and a model basing this factor might be helpful to predict the prognosis of patients with stage II-III colon cancer.